Production of e, μ and τ pairs in untagged two-photon collisions at LEP - Dova, María Teresa (1997)
The two-photon collision reaction e+e- → e+e- l+l- has been studied at √s ≈ 91 GeV using the L3 detector at LEP for l = e, μ, τ. We have analysed untagged configurations where the two photons are quasi-real. Good agreement is found between our measurements and the O(α4) QED expectation.